ChemInform Abstract: Cooperative Tandem Catalysis by an Organometallic Complex and a Metalloenzyme. Issue 28 (15th July 2014) - Denard, Carl A.; Huang, Hua; Bartlett, Mark J.; Lu, Lu; Tan, Yichen; Zhao, Huimin; Hartwig, John F.
Abstract A combination of a Hoveyda‐type catalyst and a P450 enzyme reacts cooperatively in a one‐pot process to promote a tandem reaction consisting of a metathesis/epoxidation sequence.